2012
DOI: 10.4049/jimmunol.1103021
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Tyrosine Phosphatase SHP-1 Regulates Phagolysosome Biogenesis

Abstract: The process of phagocytosis and phagosome maturation involves the recruitment of effector proteins that participate in phagosome formation and in the acidification and/or fusion with various endocytic vesicles. In the current study, we investigated the role of the Src homology region 2 domain-containing phosphatase 1 (SHP-1) in phagolysosome biogenesis. To this end, we used immortalized bone marrow macrophages derived from SHP-1–deficient motheaten mice and their wild-type littermates. We found that SHP-1 is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 70 publications
2
10
1
Order By: Relevance
“…SHP-1 is thought to inhibit phagosome acidification by acting on membrane fusion during phagosome trafficking19. Defects in phagosome acidification have also been observed in SHP-1 deficient mouse macrophages27. Our findings thus agree with recent studies that have demonstrated increased viral fusion during ADE, which leads to enhanced production of infectious DENV titres28.…”
Section: Discussionsupporting
confidence: 90%
“…SHP-1 is thought to inhibit phagosome acidification by acting on membrane fusion during phagosome trafficking19. Defects in phagosome acidification have also been observed in SHP-1 deficient mouse macrophages27. Our findings thus agree with recent studies that have demonstrated increased viral fusion during ADE, which leads to enhanced production of infectious DENV titres28.…”
Section: Discussionsupporting
confidence: 90%
“…These authors demonstrated that recognition of the parasites by Mincle triggers an inhibitory FcγR-SHP-1 axis in dendritic cells subsequently leading to down-regulation of Th 1 responses required for protective immunity to Leishmania parasites. Finally, our findings differ from a recent study showing that SHP-1 promotes non-opsonised bead-phagosome maturation [28] indicating that SHP-1 has differential regulatory functions depending on whether phagocytosis is mediated by FcγR or other receptors.…”
Section: Resultscontrasting
confidence: 99%
“…Most likely, SHP1 is the phosphatase involved in the inhibitory signalling, as it associates with CD300f in J774 and HeLa cells, and SHP1 overexpression decreases CD300f-mediated AC phagocytosis in a dose-dependent manner. In agreement, SHP1 has been shown to be recruited to Fc receptor-mediated phagosomes and negatively regulate phagocytosis 51,52 . The maximal association between CD300f and SHP1 has been reported to require several tyrosines (Y241, Y289 and Y325) 32 .…”
Section: Discussionmentioning
confidence: 84%